Painting the current picture: a national report card on drug courts and other problem-solving court - C. West Huddleston, Douglas B. Marlowe y Rachel Casebolt (My University, 2016)
This report provides an update of drug court and other problem-solving court activity in every state, territory, and district in the United States since the release of the inaugural issue of Painting the Current Picture: A National Report Card on Drug Courts and Other Problem-solving Court Programs in the United States, Volume I, Number 1 in May 2004. Volume II, Number 1 provides summary results from the 2005 National Survey on Drug Courts and Other Problem-solving Courts, conducted by the National Drug Court Institute ending on December 31, 2005. Aggregate numbers of drug courts and other problem-solving courts come from a followup survey conducted by the National Drug Court Institute ending on December 31, 2007.